Left ventricular free-wall rupture, a potentially lethal mechanical complication of coronaric angioplasty : an unusual case report: Left ventricular free-wall rupture, complication of coronaric angioplasty - Marangoni, Ludovica; Serra, Walter; Borrello, Bruno; Vezzani, Antonella; Ramelli, Andrea; Cattabiani, Maria Alberta (Acta Biomedica Atenei Parmensis, 2020)
The incidence of complications of coronary perforation varied significantly among studies probably due to population heterogeneity and interventional techniques applied in each centre.Free wall rupture, cardiac tamponade and miocardial infarction are the most  feared. The treatment of perforation remains a challenge of every cath- lab team. The management strategies range from observation to urgent operation depending on patient’s hemodynamic status, severity and location of the perforation, coronary anatomy, interventional practice and equipment in each centre and operators’ skills on-site.In this case an extracorporeal circulation and cardioplegic arrest with anterograde hot blood cardioplegia was done.A composite Dacron with autologous pericardium patch was used for left ventricular free wall rupture repair and the geometry of the left ventricle was restored. Subsequently aorta was declamped; the patient was weaned from CEC and a good spontaneous hemodynamic was recovered.